Motif dan Kepentingan China dalam Pembentukan Regional Comprehensive Economic Partnership (RCEP) - Pratama, Muhammad Ferdy; Sosa, Palwa Ibnu; Yulianto, Tegar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The establishment of the Regional Comprehensive Economic Partnership (RCEP) began because of the conflict between China and Japan. The establishment of RCEP is to create the largest trade agreement in the world because this cooperation unites regional countries with large economies. China as a country that has the largest economic level among RCEP member countries makes China control most of the market in the region. This RCEP helps China in dealing with the trade war between China and the United States, although it has not yet had a big impact. This paper uses a qualitative method and focuses on China's motives in determining the RCEP. The results of this study confirm that China's motive in determining the RCEP is to counter-balance with the TPP and China's good image to Southeast Asian countries. In addition, RCEP has a significant impact on the Chinese economy.